Absolute and Relative Vaccine Effectiveness of Primary and Booster Series of COVID-19 Vaccines (mRNA and Adenovirus Vector) Against COVID-19 Hospitalizations in the United States, December 2021–April 2022. (31st December 2022) - Lewis, Nathaniel M; Murray, Nancy; Adams, Katherine; Surie, Diya; Gaglani, Manjusha; Ginde, Adit A; McNeal, Tresa; Ghamande, Shekhar; Douin, David J; Talbot, H Keipp; Casey, Jonathan D; Mohr, Nicholas M; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) vaccine effectiveness (VE) studies are increasingly reporting relative VE (rVE) comparing a primary series plus booster doses with a primary series only. Interpretation of rVE differs from traditional studies measuring absolute VE (aVE) of a vaccine regimen against an unvaccinated referent group. We estimated aVE and rVE against COVID-19 hospitalization in primary-series plus first-booster recipients of COVID-19 vaccines. Methods: Booster-eligible immunocompetent adults hospitalized at 21 medical centers in the United States during December 25, 2021–April 4, 2022 were included. In a test-negative design, logistic regression with case status as the outcome and completion of primary vaccine series or primary series plus 1 booster dose as the predictors, adjusted for potential confounders, were used to estimate aVE and rVE. Results: A total of 2060 patients were analyzed, including 1104 COVID-19 cases and 956 controls. Relative VE against COVID-19 hospitalization in boosted mRNA vaccine recipients versus primary series only was 66% (95% confidence interval [CI], 55%–74%); aVE was 81% (95% CI, 75%–86%) for boosted versus 46% (95% CI, 30%–58%) for primary. For boosted Janssen vaccine recipients versus primary series, rVE was 49% (95% CI, −9% to 76%); aVE was 62% (95% CI, 33%–79%) for boosted versus 36% (95% CI, −4% to 60%) for primary. Conclusions: Vaccine booster doses increased protection against COVID-19 hospitalization compared with a primary series. Comparing rVE measures across studies can lead to flawed interpretations of the added value of a new vaccination regimen, whereas difference in aVE, when available, may be a more useful metric. Abstract : Although relative vaccine effectiveness can be a useful measure to understand incremental benefit of a vaccine booster regimen compared with a primary series alone, absolute vaccine effectiveness estimates are needed to fully understand their benefit.